PENERAPAN METODE PROBLEM SOLVING PADA PEMBELAJARAN PAI UNTUK MATERI IMAN KEPADA QADHA DAN QADAR DI KELAS XII MIPA 1 SMA NEGERI 1 KOTO GASIB - Mahpuzo Mahpuzo (Jurnal Pendidikan, 2020)
This study aims to determine students' understanding through the use of problem solving methods in learning of PAI for material on faith in qadha and qadar.The research subjects were students of class XII MIPA 1 SMA Negeri 1 Koto Gasib with a total of 31 students. The research method used is Classroom Action Research (PTK). The research design consisted of 2 cycles.Data collection techniques in this study using tests, observation, interviews and documentation studies.Quantitative data analysis uses a statistical approach and qualitative data uses a logical approach. For learning outcomes, there was a significant increase in each cycle, namely: cycle I with a total value of 2243 with an average score of 77.34 and observations proved that students had started to be active but students' understanding of the material was still low. Whereas in the second cycle the total value was 2555 with an average value of 88.10 and the results of observations made through the observation sheet proved that in the second cycle the students had seen that they were very active in their learning and the value obtained was above the minimum score achievement criteria. has been determined.